INVESTIGATION OF THE INFLUENCE OF ELECTRIC FIELD ON THE ANISOTROPY OF NEMATIC LIQUID CRYSTALS BY MEANS OF X-RAY INTERFEROMETRIC METHOD - Gasparyan, L.G.; Mkrtchyan, V.P.; Dadalyan, T.K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The refractive index of nematic liquid crystal (NLC) E7 in the X-ray spectral range using the X-ray interferometric method, was measured experimentally. It was shown that NLC E7 is anisotropic medium for X-rays. This method is sensitive to reorientation of the molecules of liquid crystals and allows to measure the refractive index of homogeneously aligned NLC layer, when the molecules are reoriented under the influence of external electric field.
Keywords: nematic liquid crystal, LLL spectroscopy